(Solid + liquid) phase equilibrium for the ternary system (K2CO3-Na2CO3-H2O) at T = (323.15, 343.15, and 363.15) K. (May 2017) - Yin, Congcong; Liu, Meitang; Yang, Jing; Ma, Hongwen; Luo, Zheng
Highlights: Phase equilibrium of the system K2 CO3 -Na2 CO3 -H2 O at (323.15, 343.15 and 363.15) K. The salting-out effect was enhanced with the increasing of temperature. The densities of liquid phase were investigated and compared with calculated value. Abstract: In order to provide a theoretical basis and fundamental data for industrial utilization of insoluble potassium rocks to produce potassium salts, the phase equilibrium of the ternary system K2 CO3 -Na2 CO3 -H2 O at 323.15 K, 343.15 K and 363.15 K was determined using the isothermal dissolution equilibrium method. According to the experimental results of salt solubility, the phase diagrams were constructed and the crystallization zones are discussed in detail. All of the solubility isotherms at 323.15 K, 343.15 K and 363.15 K consist of two invariant points, three univariant curves and three crystallization fields corresponding to Na2 CO3 ·H2 O, K2 CO3 ·Na2 CO3 and K2 CO3 ·1.5H2 O, respectively. The densities of the liquid phase of the ternary systems were investigated as well.